The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1029/ja093ia06p05965
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of OGO 6 measured thermospheric temperatures with the MSIS‐86 empirical model

Abstract: The thermospheric temperatures measured by the Fabry-Perod interferometer on the OGO 6 satellite are found to be reasonably represented by the mass spectrometer/incoherent scatter 1986 (MSIS-86) empirical model except for two anomalies, one in the South Atlantic and the other near noon local time. These anomalies are likely due to measurement problems. The OGO 6 temperature data were not used in the generation of the MSIS models, so this is an independent comparison of measured and model temperatures. The meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Neither altitude nor solar cycle variations are included in the model due to lack of data coverage, and it is only valid above about 220 km where the data coverage is best and viscosity reduces the wind variation with height. The HWM87 predictions for low and mid‐latitude winds are similar to previously published ground‐based measurements [ Hedin et al , 1988]. Recently, satisfactory agreement has been obtained between the HWM87 predictions and both ground‐based [ Miller et al , 1990; Biondi et al , 1990b; Oliver et al , 1990] and space‐based [ Burrage et al , 1990] wind measurements.…”
Section: Thermospheric Modelingsupporting
confidence: 80%
See 2 more Smart Citations
“…Neither altitude nor solar cycle variations are included in the model due to lack of data coverage, and it is only valid above about 220 km where the data coverage is best and viscosity reduces the wind variation with height. The HWM87 predictions for low and mid‐latitude winds are similar to previously published ground‐based measurements [ Hedin et al , 1988]. Recently, satisfactory agreement has been obtained between the HWM87 predictions and both ground‐based [ Miller et al , 1990; Biondi et al , 1990b; Oliver et al , 1990] and space‐based [ Burrage et al , 1990] wind measurements.…”
Section: Thermospheric Modelingsupporting
confidence: 80%
“… Hedin and Thuillier [1988] obtained very good agreement between MSIS‐86 predictions and optical Fabry‐Perot temperature data from the OGO‐6 satellite, which were not incorporated in the MSIS models. The measured temperatures were only 16K below the MSIS‐86 temperatures on average.…”
Section: Thermospheric Modelingmentioning
confidence: 85%
See 1 more Smart Citation
“…The accuracy of the neutral temperature calculated by MSIS also influences the results of the present study. Hedin and Thuillier [1988] have shown that MSIS-86 reproduced temperature data from the OGO 6 satellite to within about 100 K. Such temperature uncertainties were found to significantly affect the spectral fit of the 1 PG band but had a negligible impact on the fitted N I multiplet intensities. The electron impact cross sections for the N I multiplets and N 2 1 PG were obtained from laboratory studies.…”
Section: Model Uncertaintiesmentioning
confidence: 93%
“…This version has been extensively used for comparing model predictions with measurements; see [1], [6], [14] for instance. The MSIS model is based on extensive insitu data measurements from numerous rocket probes and satellites (OGO 6, San Marco 3, AEROS-A, AE-C, AE-D, AE-E, ESRO 4, and DE 2) as well as ground-based incoherent scatter radars (Millstone Hill, St. Santin, Arecibo, Jicamarca, and Malvern).…”
Section: The Atmosphere Models Msismentioning
confidence: 99%